Rozwiązanie:
Zadanie [tex]1.[/tex]
[tex]d)[/tex]
[tex]log_{6}10-log_{6}\frac{5}{18} +log_{6}\sqrt{6} =log_{6}(\frac{10}{\frac{5}{18} } )+log_{6}\sqrt{6}=log_{6}(10 \cdot \frac{18}{5} )+log_{6}\sqrt{6}=log_{6}36+log_{6}\sqrt{6}=2+\frac{1}{2}=\frac{5}{2}[/tex]
Zadanie [tex]2.[/tex]
[tex]b)[/tex]
[tex]log_{8}x=\frac{log_{5}3-log_{5}75}{log_{2}48-log_{2}6} \\log_{8}x=\frac{log_{5}\frac{3}{75} }{log_{2}\frac{48}{6} } \\log_{8}x=\frac{log_{5}\frac{1}{25} }{log_{2}8} \\log_{8}x=\frac{-2}{3} \\x=8^{-\frac{2}{3} }=(\frac{1}{8} )^{\frac{2}{3} }=\frac{1}{\sqrt[3]{64} } =\frac{1}{4}[/tex]
[tex]c)[/tex]
[tex]log_{0,1}x=\frac{log_{3}18-log_{3}2}{log_{3}6-log_{3}18} \\log_{0,1}x=\frac{log_{3}\frac{18}{2} }{log_{3}\frac{6}{18} } \\log_{0,1}x=\frac{log_{3}9}{log_{3}\frac{1}{3} } \\log_{0,1}x=\frac{2}{-1} \\x=(\frac{1}{10})^{-2} =100[/tex]